IMMU-50. GLIOBLASTOMA MANIPULATES HEMATOPOIETIC STEM CELL DIFFERENTIATION OUTCOMES AND DRIVES ALTERED IMMUNE RECONSTITUTION. (12th November 2021) - Dean, Bayli DiVita; Wildes, Tyler; Dean, Joseph; Shin, David; Francis, Connor; Font, Laura Falceto; Moore, Ginger; Flores, Catherine
Abstract: INTRODUCTION: Bone marrow-derived hematopoietic stem and progenitor cells (HSPCs) give rise to the cellular components of the immune system. Unfortunately, immune reconstitution from HSPCs are negatively impacted by solid cancers, including high-grade gliomas. For example, an expansion of myeloid progenitor cells has been previously described across several cancers that originate outside the CNS. A similar expansion of MDSCs coupled with diminished T cell function has also been described in the peripheral blood of patients with newly-diagnosed GBM. Alterations in both lymphoid and myeloid compartments due to CNS malignancy led us to determine how intracranial gliomas impact HSPCs in both their capacity to reconstitute the immune compartment and in their cell fate determination. This is important to better understand the impact of gliomas on immunity and how we can leverage these findings to better develop cellular immunotherapeutics. METHODS: HSPCs were isolated from bone marrow of C57BL/6 mice with orthotopic KR158B glioma, or age-matched naïve mice. Experiments were conducted to compare relative changes in: gene expression (RNA-sequencing), precursor frequencies, cell fate determination, and cellular function of cells derived from HSPCs of glioma-bearing mice. RESULTS: RNA-sequencing revealed 700+ genes whose expression was significantly up- or downregulated in HSPCs from glioma-bearing mice, particularly those involved with stemness and metabolic activity. Importantly, HSPCs from glioma-bearing mice expressed upregulation of genes involved in myelopoiesis relative to naïve mice. This was coupled with an expansion of granulocyte macrophage precursors (GMPs), the progenitors to gMDSCs. Next, differentiation assays revealed that HSPCs from glioma-bearing mice had higher propensity of differentiating into MDSC under homeostatic conditions relative to controls both in vitro and in vivo. Furthermore, mice bearing intracranial gliomas possess an expansion of MDSCs which are more suppressive on T cell proliferation and hinders T cell-mediated tumor cell killing relative to MDSCs derived from naïve control mice.